Challenges to Sustaining University-Community Partnerships in War-Torn, Northern Uganda: Investigating Resistance, Negative Stereotyping, and Gender Bias in Agricultural Students’ Attachments - Richie Roberts; Craig M. Edwards (Journal of International Agricultural and Extension Education, 2017)
Gulu Town (Gulu) served as a site of refuge for many during northern Uganda’s armed conflict that spanned from 1986 to 2006. Since then, Gulu transitioned into a region with sprawling slums and deteriorating social conditions. To combat these trends, the Faculty of Agriculture and Environment (FAE) at Gulu University adopted a development approach emphasizing community transformation. The FAE conceptualizes community transformation as the building of Gulu community members’ capacity to transition from a subsistence agrarian lifestyle to one more economically sustainable. One mechanism the FAE uses to enact their commitment to community transformation are university-community partnerships established to facilitate agricultural student attachments, or internships. Because of the myriad ways university-community partnerships are manifested, we examined the challenges to sustaining such partnerships in this post-conflict region. When interpreting findings through Foucauldian (1972) discourse theory, three themes emerged: (a) resistance, (b) reinforcement of stereotypes, and (c) gender bias. Moving forward, we recommend training opportunities be developed to promote more collaborative, contextually grounded strategies to overcome the challenges and enhance the partnerships such that all participants benefit.
Keywords: attachments; gender bias; Uganda; university-community partnerships